2007
DOI: 10.1159/000108110
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs and the Risk of Parkinson Disease

Abstract: Background: Several lines of evidence suggest a role of inflammatory processes in Parkinson disease, although it is still unclear whether inflammation is a cause or rather a consequence of neurodegeneration. Methods: In a prospective population-based cohort study among 6,512 participants aged ≧55 years, with repeated in-person examination, we evaluated the association between cumulative use of nonsteroidal anti-inflammatory drugs (NSAIDs) and the risk of Parkinson disease. Complete information on filled prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 25 publications
1
45
0
2
Order By: Relevance
“…Therefore, no indication of protection from ASA or other NSAIDs was recognized through this study. Bornebroek and colleagues 40 obtained similar results. They did a prospective population-based cohort study among 6,512 participants of 55 years old or older, and found no association between the use of NSAIDs and risk of developing PD.…”
Section: Epidemiological Studies On the Regular Use Of Nsaids And Thementioning
confidence: 64%
“…Therefore, no indication of protection from ASA or other NSAIDs was recognized through this study. Bornebroek and colleagues 40 obtained similar results. They did a prospective population-based cohort study among 6,512 participants of 55 years old or older, and found no association between the use of NSAIDs and risk of developing PD.…”
Section: Epidemiological Studies On the Regular Use Of Nsaids And Thementioning
confidence: 64%
“…A meta-analysis of results from all three cohorts gave a RR estimate of 0.74 (95% CI 0.58-0.93) for ever versus never use of non-aspirin NSAID [558]. In contrast, the Rotterdam prospective study reported no association between NSAIDs and PD [559].…”
Section: Inflammationmentioning
confidence: 98%
“…Another study conducted by the same group in the American Cancer Society cohort, however, suggested protection only for daily users of one specific NSAID, ibuprofen, and not aspirin [18]. A much smaller Dutch cohort found no association or a small risk increase among ever users of NSAIDs, but only six PD cases reported use of these medications for more than 1 year [26].…”
mentioning
confidence: 95%
“…Thus, studies assessing shorter term use, use at older age or use during short windows prior to disease onset, may be missing the most relevant time frames for arresting the inflammatory process. For example, this might explain the failure to detect a protective effect in some studies [26,29]. Evaluating current use is especially problematic when studying NSAID use in the context of PD since the preclinical phase of PD is estimated to be long [33,34] and cases may increase pain reliever use in the years leading up to actual diagnosis as a result of preclinical PD.…”
mentioning
confidence: 99%
See 1 more Smart Citation